2021
DOI: 10.1101/2021.01.15.426618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repurposing of an Antifungal Drug against Gastrointestinal Stromal Tumors

Abstract: Drug discovery is an important research area to improve human health. Currently, treatment of gastrointestinal stromal tumors (GISTs) is unsuccessful due to drug-resistance, hence, there is a demand for alternatives. Often, there is limited time available for toxicological assessments and a lack of safer drugs. It is possible to identify new drugs from existing approved drugs possessing another purpose in the clinical lines. In this study, virtual screening of some Food and Drug Administration (FDA-USA) approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Levosimendan shows anti-cancer activity against various cancers by directly inhibiting RIOK1 and RNA processing enzymes ( Lim et al, 2019 ). Similarly, Arulanandam CD et al (2021) suggested itraconazole as a better inhibitor of platelet-derived growth factor receptor alpha (PDGFRA) compared to other antifungal drugs for treating gastrointestinal stromal tumors (GISTs) ( Arulanandam et al, 2021 ).…”
Section: Approaches Used For Drug Repurposing In Cancer Therapymentioning
confidence: 99%
“…Levosimendan shows anti-cancer activity against various cancers by directly inhibiting RIOK1 and RNA processing enzymes ( Lim et al, 2019 ). Similarly, Arulanandam CD et al (2021) suggested itraconazole as a better inhibitor of platelet-derived growth factor receptor alpha (PDGFRA) compared to other antifungal drugs for treating gastrointestinal stromal tumors (GISTs) ( Arulanandam et al, 2021 ).…”
Section: Approaches Used For Drug Repurposing In Cancer Therapymentioning
confidence: 99%